2002
DOI: 10.1046/j.1523-1755.2002.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel association between residual renal function and left ventricular hypertrophy in peritoneal dialysis patients

Abstract: Other than anemia, hypoalbuminemia and arterial pulse pressure, this study demonstrates an important, novel association between the degree of RRF and severity of LVH in ESRF patients undergoing long-term CAPD. Prospective studies are needed to define if indeed there is a cause-effect relationship between this association, to evaluate if a decline in residual GFR is independently associated with an increase in LVMi, and to determine whether treatment directed at preserving RRF will reduce the severity of LVH, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
151
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(161 citation statements)
references
References 43 publications
5
151
3
2
Order By: Relevance
“…Wang et al found that left ventricular mass increased in peritoneal dialysis patients who had lower glomerular filtration rates. 9 However, these authors found similar end diastolic diameters among the assessed groups, which differs from the findings in our study. One of the possible reasons for these different findings could be due to the type of dialysis, while another reason may be that the authors did not correlate modifications in the left ventricle with the residual 24-hour urinary volume of their patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Wang et al found that left ventricular mass increased in peritoneal dialysis patients who had lower glomerular filtration rates. 9 However, these authors found similar end diastolic diameters among the assessed groups, which differs from the findings in our study. One of the possible reasons for these different findings could be due to the type of dialysis, while another reason may be that the authors did not correlate modifications in the left ventricle with the residual 24-hour urinary volume of their patients.…”
Section: Discussioncontrasting
confidence: 99%
“…5 During the conservative management of patients with CKD, 6 it was observed that the decline in the glomerular filtration rate was associated with left ventricular hypertrophy (LVH). [7][8][9][10][11] The presence of LVH, in turn, constitutes an important independent factor for cardiovascular risk in patients with CKD. 7,8,12,13 Patients in renal replacement therapy (stage V) 6 may have larger or smaller residual renal function (RRF) declines depending on the diastolic method used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the need for dietary and fluid restriction is reduced, which may partly explain their better nutritional state (8) and quality of life (9). In terms of clinical outcomes, the degree of RRF has been inversely associated with left ventricular hypertrophy, independent of blood pressure or anemia level (10). Moreover RRF has been associated with improved survival in hemodialysis (HD) and peritoneal dialysis (PD) patients (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, a significant relationship was found between total KtV and total UF. LVH has been inversely related to residual KtV, with higher LVH in anuric patients than in patients with residual diuresis 24,25 . The CANUSA study showed that each 250 ml of urine shows a 36% decrease in overall mortality 26,27 .…”
Section: Discussionmentioning
confidence: 99%